Deep phenotyping of the unselected COPSAC2010 birth cohort study. Issue 12 (December 2013) - Bisgaard, H.; Vissing, N. H.; Carson, C. G.; Bischoff, A. L.; Følsgaard, N. V.; Kreiner‐Møller, E.; Chawes, B. L. K.; Stokholm, J.; Pedersen, L.; Bjarnadóttir, E.; Thysen, A. H.; Nilsson, E.; et al.
Summary Background We hypothesize that perinatal exposures, in particular the human microbiome and maternal nutrition during pregnancy, interact with the genetic predisposition to cause an abnormal immune modulation in early life towards a trajectory to chronic inflammatory diseases such as asthma and others. Objective The aim of this study is to explore these interactions by conducting a longitudinal study in an unselected cohort of pregnant women and their offspring with emphasis on deep clinical phenotyping, exposure assessment, and biobanking. Exposure assessments focus on the human microbiome. Nutritional intervention during pregnancy in randomized controlled trials are included in the study to prevent disease and to be able to establish causal relationships. Methods Pregnant women from eastern Denmark were invited during 2008–2010 to a novel unselected 'COPSAC2010' cohort. The women visited the clinic during pregnancy weeks 24 and 36. Their children were followed at the clinic with deep phenotyping and collection of biological samples at nine regular visits until the age of 3 and at acute symptoms. Randomized controlled trials of high‐dose vitamin D and fish oil supplements were conducted during pregnancy, and a trial of azithromycin for acute lung symptoms was conducted in the children with recurrent wheeze. Results Seven hundred and thirty‐eight mothers were recruited from week 24 of gestation, and 700 of their children were included in the birth cohort. The cohort has an over‐representation of atopic parents. The participant satisfaction was high and the adherence equally high with 685 children (98%) attending the 1 year clinic visit and 667 children (95%) attending the 2 year clinic visit. Conclusions The COPSAC2010 birth cohort study provides longitudinal clinical follow‐up with highly specific end‐points, exposure assessments, and biobanking. The cohort has a high adherence rate promising strong data to elucidate the interaction between genomics and the exposome in perinatal life leading to lifestyle‐related chronic inflammatory disorders such as asthma.